Curcumin Down-Regulates CD44 Marker Expresion and Inhibits the Growth of Tumorsphere in 3D Culture Condition of Gastric Cancer Cell line MKN45 - Hung, Nguyen Phu; Thanh Huong, Le Thi; Thanh, Nguyen Trung (VNU Journal of Science: Natural Sciences and Technology; Vol 36 No 3DO - 10.25073/2588-1140/vnunst.5075, 2020)
Stomach cancer is the fifth most common cancer in the world. In Vietnam, the number of deaths by stomach cancer ranks third after lung cancer and liver cancer. Finding naturally occurring compounds that can effectively inhibit tumor is very important in the treatment of cancer, especially for developing countries as Vietnam. This study showed that curcumin has ability to inhibit stomach cancer evaluated on a 3D culture model. This is a model that has many advantages compared to the traditional model (2D) for screening of new drugs. Research results show that curcumin had significantly reduced the expression of CD44 stem cell marker on the gastric cancer. Curcumin inhibited the formation of tumorsphere in non-adhering culture conditions 3D. In addition, curcumin reduced the size of the tumorspheres compared to the control.